AKUNTABILITAS PENDIDIKAN BERBASIS AGAMA, FILSAFAT, PSIKOLOGI, DAN SOSIOLOGI - Khoirul Anwar; Iman Saifullah; Muhammad Al Mighwar; Ujang Nurjaman (Fakultas Agama Islam Universitas Wiralodra, 2022)
This study aims to describe and analyze the what, why, and how of education accountability based on religion, philosophy, psychology, and sociology. The results of this study are that the education accountability: (1) based on religion is a spiritual responsibility to God as a result of an educational act, which should be done fairly, ihsan, satisfactorily, not cheating, not violating the rules, and not contradicting; (2) based on philosophy is intellectual accountability to the rules of logical thinking as a result of an educational act, which should be carried out by means of essential, perennial, pragmatic and progressive, and reconstructional thinking; (3) based on psychology is an emotional responsibility to a sense of humanity as a result of an educational act, which should be done by considering aspects of the nature, behavior, and the right situation around it; and (4) based on sociology is social responsibility to the position of society as a result of an educational act, which should be done by fulfilling the functional needs of the community, both political stratification, economy and social status